Additive Manufacturing of Gradient and Multimaterial Components - Karg, Michael; Laumer, Tobias; Schmidt, Michael (Archive of COMA 2013, 2013)
In the paper first results regarding the realisation of gradient and multi-material parts manufactured by Laser Beam Melting in powder bed of metals and polymers are published. Gradient properties of additively manufactured metal parts can be achieved by varying the composition of alloying components in the powder and adapting process strategies. As an alternative to atomizing prealloyed materials, mixtures of different powders are investigated. For realizing multi-material-parts from polymers, at first relevant material properties concerning compatibility have to be analysed. Therefore the paper shows the main requirements for compatibility between different materials and also first results regarding the compatibility of polymer powders and possible combinations for the manufacturing of multi-material components by laser beam melting of polymers.<br style=" font-style: normal; font-variant: normal; font-weight: normal; letter-spacing: normal; line-height: normal; orphans: 2; text-align: -webkit-auto; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-size-adjust: auto; -webkit-text-stroke-width: 0px; " />
Keywords: Laser Beam Melting in Powder Bed; New Materials; Additive Manufacturing

Analysis of temperature gradients during simultaneous laser beam melting of polymers - Laumer, Tobias; Stichel, Thomas; Amend, Philipp; Roth, Stephan; Schmidt, Michael (Physics Procedia, 2014)
By simultaneous laser beam melting (SLBM), different polymer powders can be processed to multi-material parts, which offers the potential to enlarge the field of application for conventional LBM. In a SLBM process, a powder bed consisting of different polymers and therefore with different melting and crystallization temperatures is deposited. Besides the use of infrared emitters for preheating the lower melting polymer, a CO2 laser distributes the necessary preheating temperature of the higher melting polymer. In the last step, a thulium fibre laser distributes the energy necessary for melting the two preheated powders simultaneously. In order to analyze the temperature gradients of the process on the powder surface and in deeper layers, a high-resolution thermal imaging system and thermocouples are used.
Created from Fastlane, Scopus look-up
Keywords: Additive manufacturing; Multi-material parts; Process qualification; Simultaneous laser beam melting

Analysis of the influence of different flowability on part characteristics regarding the simultaneous laser beam melting of polymers - Laumer, Tobias; Stichel, Thomas; Raths, Max; Schmidt, Michael (Physics Procedia, 2016)
Powder based Additive Manufacturing technologies offer huge potential for building parts with almost no geometrical restrictions, but both the process controlling as well as the part properties are strongly dependent on different material characteristics of the material, like the flowability. In this work, different weight percentages of nano-scaled silica dioxide particles (Aerosil®) are admixed to pure polyethylene and polypropylene powder and the resulting flowability is determined. Besides using the Hausner ratio as standardized value, the degree of coverage is introduced as a new characteristic to quantify the powder flowability. The degrees of coverage are compared to the Hausner ratios to allow a discussion and evaluation about the different characteristic values. Additionally, tensile bars consisting of polypropylene are generated to determine the porosity by cross sections and the mechanical part properties by tensile testing. As mechanical part properties, the tensile strength and elongation at break are determined and the effects of different powder flowability on these properties are analyzed.
Created from Fastlane, Scopus look-up
Keywords: Additive Manufacturing; Laser Beam Melting of Polymers; Material Qualification

Analysis of the interaction between the temperature field and the weld seam morphology in laser transmission welding by using two different discrete laser wavelengths - Geissler, Bastian; Laumer, Tobias; Wuebbeke, Andrea; Lakemeyer, Patrick; Frick, Thomas; Schoeppner, Volker; Schmidt, Michael (Journal of Laser Applications, 2018)
Laser transmission welding is a non-contact and efficient process technology for joining thermoplastic polymers. In the conventional process, laser sources in the wavelength range of 1 μm are usually used. Therefore, most of the laser radiation is transmitted through the upper joining partner and absorbed only in the lower joining partner. As a result, the possibilities to influence the temperature field especially in the upper joining partner are limited. To overcome these limitations, an additional thulium fiber-laser with a wavelength of 1.94 μm is used in this study and coaxially aligned with a diode laser. The use of an additional thulium fiber-laser leads to a significant absorption in the upper joining partner. Through this approach, it is shown that the temperature field and the weld seam geometry can be influenced by using these two different discrete laser wavelengths. Depending on the intensity distribution of both lasers, an increase of the size of the heat affected zone in the upper joining partner can be observed. In order to develop a better process understanding, a thermal finite element model is built up and verified by comparing the calculated size of the heat affected zone for different process parameters with the experimental data. The model is able to represent the influence of both laser sources on the temperature field and is used to calculate characteristics of the temperature field, such as maximum temperatures or cooling rates. The characteristics are then used to explain the weld seam morphology, such as occurrence and size of spherulitic structures in the weld seam.
Created from Fastlane, Scopus look-up
Keywords: laser transmission welding; polypropylene; temperature field simulation; weld seam morphology

Analysis of the weld seam morphology of polypropylene in laser transmission welding - Geissler, Bastian; Laumer, Tobias; Wuebbeke, Andrea; Frick, Thomas; Schoeppner, Volker; Schmidt, Michael (Journal of Manufacturing Science and Engineering, 2018)
Laser transmission welding is a well-known joining technology for welding thermoplastics. Although the process is already used industrially, fundamental process-structure-property relationships are not fully understood and are therefore the subject of current research. One aspect of these mentioned process-structure-property relationships is the interaction between the temperature field during the welding process, the weld seam morphology of semi-crystalline thermoplastics, and the weld seam strength. In this study, the influence of the line energy on the weld seam morphology of polypropylenes is analyzed. For this purpose, the size of spherulites in the weld seam is investigated, as well as different occurring phases of polypropylene (a- and b-phase). It is shown that both the spherulite size of the a-phase and the amount of b-phase increase with increasing line energy. For the explanation and discussion of the results, a temperature-dependent thermal simulation model is used to derive characteristic attributes of the temperature field (maximum temperatures, cooling rates, temperature gradients).
Created from Fastlane, Scopus look-up

A Round Robin study for Selective Laser Sintering of polyamide 12: Microstructural origin of the mechanical properties - Stichel, Thomas; Frick, Thomas; Laumer, Tobias; Tenner, Felix; Hausotte, Tino; Merklein, Marion; Schmidt, Michael (Optics and Laser Technology, 2017)
The mechanical and microstructural investigation of polymer parts (polyamide 12) fabricated by Selective Laser Sintering as part of a Round Robin initiative is presented. The paper focuses on the microstructural analysis of the Round Robin samples and their evaluation regarding their effect on mechanical properties with respect to each other. Therefore optical microscopy on microtomed samples, X-ray computed tomography and Differential Scanning Calorimetry is used to determine the morphology of residual particle cores and of internal pores.The mechanical tensile testing revealed a high variability of the ductility of the samples among the used machines and a distinctive anisotropic mechanical response. Especially the quite brittle characteristic along the building direction has shown to be still a crucial challenge for the process. However, one machine delivered samples with outstanding ductility with total elongation values of about 21% along the building direction and of about 32% planar to the layer. This result was back traced to a distinctive pore and residual particle morphology which is characterized by low pore concentration, the absence of coplanar pore or residual particle arrangements and the highest degree of particle melting measured. Furthermore, the analysis depicts that both features, pores and residual particles, contribute to the mechanical properties significantly and that they are not necessarily linked since they can vary independently in a certain range depending on the machine configuration.
Keywords: Additive manufacturing; Polymers; Polyamide-12; Selective Laser Sintering; Round Robin

A Round Robin study for selective laser sintering of polymers: Back tracing of the pore morphology to the process parameters - Stichel, Thomas; Frick, Thomas; Laumer, Tobias; Tenner, Felix; Hausotte, Tino; Merklein, Marion; Schmidt, Michael (Journal of Materials Processing Technology, 2018)
The mechanical properties of polymer parts built by Selective Laser Sintering are strongly related to the internal microstructure which differs with the applied production parameters. The paper focuses on the back tracing of the pore morphology of laser sintered polyamide-12 samples to the process parameters. Therefore, a data base is used which is supplied by a Round Robin initiative and includes mechanical tensile tests and the microstructural analysis of the pore morphology of several different sample charges built with different machines. The pore morphologies (porosity, pore density, pore shape and pore arrangement) measured by X-ray computed tomography are compared and discussed regarding the employed parameters and the resulting mechanical properties.The investigations point out that pore density is a superior indicator than porosity for mechanical issues. This is especially valid along the build direction since pore morphology has shown to be strongly anisotropic. Moreover, the analysis revealed that pore density is strongly affected by the process temperature, which is proved to be essential for the fabrication of mechanical robust parts using Selective Laser Sintering.
Keywords: Additive manufacturing; Polymers; Polyamide-12; Selective laser sintering; Round Robin; Porosity; Pore density; X-ray computed tomography

Characterization of temperature-dependent optical material properties of polymer powders - Laumer, Tobias; Stichel, Thomas; Bock, Thomas; Amend, Philipp; Schmidt, Michael (AIP Conference Proceedings, 2015)
In former works, the optical material properties of different polymer powders used for Laser Beam Melting (LBM) at room temperature have been analyzed. With a measurement setup using two integration spheres, it was shown that the optical material properties of polymer powders differ significantly due to multiple reflections within the powder compared to solid bodies of the same material. Additionally, the absorption behavior of the single particles shows an important influence on the overall optical material properties, especially the reflectance of the powder bed. Now the setup is modified to allow measurements at higher temperatures. Because crystalline areas of semi-crystalline thermoplastics are mainly responsible for the absorption of the laser radiation, the influence of the temperature increase on the overall optical material properties is analyzed. As material, conventional polyamide 12 and polypropylene as new polymer powder material, is used. By comparing results at room temperature and at higher temperatures towards the melting point, the temperature-dependent optical material properties and their influence on the beam-matter interaction during the proceb are discubed. It is shown that the phase transition during melting leads to significant changes of the optical material properties of the analyzed powders.
CRIS-Team Scopus Importer:2023-03-07
Keywords: Laser Beam Melting; Material Qualification; Optical Material Properties; Polymers

Correlation Analysis of Different Building Parameters on the Part Properties of Parts Built by Simultaneous Laser Beam Melting of Polymers - Laumer, Tobias; Stichel, Thomas; Schmidt, Michael (Fraunhofer Direct Digital Manufacturing Conference DDMC 2016: Conference Proceedings, 2016)
Simultaneous Laser Beam Melting of polymers (SLBM) allows the generation of multi-material components, consisting of different thermoplastic polymers, within one additive building process. Besides the common advantages of conventional Laser Beam Melting (LBM), multi-material components built by SLBM can fulfill different product requirements like different chemical resistances or haptic material properties within a single part. To achieve such parts, different powder materials are deposited next to each other and preheated a few degrees below their melting temperatures by infrared emitters and laser radiation (λ = 10.60 µm), before in the last step the preheated powders are molten simultaneously by an additional laser source (λ = 1.94 µm). In this paper, different polymer powders like polypropylene (PP) and polyamide 12 (PA12) are used for the generation of multi-material specimens. By varying different building parameters according to a specified design of experiments, their influence on the part properties is analyzed. Important building parameters are the intensity and the irradiation time of the laser beam used for melting the preheated powders. Besides using tensile tests to determine the tensile strength and the elongation at break, the average part height in dependence of the energy input is analyzed. The overall aim is to specify the correlation between different building parameters regarding the energy deposition on the resulting part propertie

Detecting surface roughness on SLS parts with various measuring techniques - Launhardt, Martin; Wörz, Andreas; Loderer, Andreas; Laumer, Tobias; Drummer, Dietmar; Hausotte, Tino; Schmidt, Michael (Polymer Testing, 2016)

Fundamental investigation of laser beam melting of polymers for additive manufacture - Laumer, Tobias; Wudy, Katrin; Drexler, Maximilian; Amend, Philipp; Drummer, Dietmar; Schmidt, Michael; Roth, Stephan (Journal of Laser Applications, 2014)
By selective laser sintering (SLS), polymer powders are molten layer by layer to build conventional prototypes or parts in small series with geometrical freedom that cannot be achieved by other manufacturing technologies. The SLS process is mainly defined by the beam-matter interaction between powder material, laser radiation and different material characteristics by itself. However the determination of these different material characteristics is problematic because powder material imposes certain requirements that cannot sufficiently be provided by conventional measurement methods. Hence new fundamental investigation methods to determine the optical and thermal material characteristics like the thermal diffusivity, thermal conductivity, or the influence of different heating rates on the melting behavior are presented in this paper. The different analysis methods altogether improve the process of understanding to allow recommendations for the future process controlling. (C) 2014 Laser Institute of America.
Keywords: additive manufacturing; laser beam melting of polymers; multi-material parts

Fundamental investigation of laser beam melting of polymers for additive manufacture (vol 26, 042003, 2014) - Laumer, Tobias; Wudy, Katrin; Drexler, Maximilian; Amend, Philipp; Drummer, Dietmar; Schmidt, Michael; Roth, Stephan (Journal of Laser Applications, 2015)

Generation of multi-material parts with alternating material layers by Simultaneous Laser Beam Melting of polymers - Laumer, Tobias; Stichel, Thomas; Fanselow, Stephanie; Koopmann, Jonas; Amend, Philipp; Schmidt, Michael (International Conference on Additive Technologies - ICAT 2014, 2014)
By using Additive Manufacturing technologies, like Laser Beam Melting (LBM) of polymers, parts can be realized within single days and necessary modifications can be quickly adapted. With increasing complexity, products are often made out of different polymer materials and the need for multi-material parts is an increasing industry requirement, which cannot be fulfilled by the single material parts realizable by LBM. Therefore, Simultaneous Laser Beam Melting (SLBM) as a new Additive Manufacturing technology offers the possibility to build parts consisting of different polymer materials. The realizable parts combine different material properties, like differing stiffness or chemical resistances, within a single part. Up to now, different materials are deposited next to each other on the building platform, thus the boundary surface between the different polymers is orientated perpendicular to the building direction. For this paper, the polymer powders are alternated in building direction. Thus, the boundary surface is orientated horizontally and is larger, both influencing the boundary surface and resulting part properties, which are analyzed by a high-resolution thermal imaging system and by cross sections.
Keywords: Additive Manufacturing; Simultaneous Laser Beam Melting; Multi-Material Parts

Herstellung von Polyolefinstrahlschmelzmaterialien mittels Schmelzeemulgieren zum Einsatz in der additiven Fertigung - Schmidt, Jochen; Fanselow, Stephanie; Wirth, Karl-Ernst; Peukert, Wolfgang; Hiller, Saskia; Laumer, Tobias; Schmidt, Michael (Neue Entwicklungen in der Additiven Fertigung, 2015)
Im Rahmen dieses Beitrags wird das Schmelzeemulgieren als Verfahren zur Herstel-lung von Polymermikropartikeln vorgestellt. In diesem Prozess wird zunächst ein Polymergranulat in einer kontinuierlichen Phase in Gegenwart geeigneter Additive in einem Rührbehälter aufgeschmolzen, die Rohemulsion in einer Rotor-Stator-Einheit feinemulgiert und anschließend zu einer Suspension abgekühlt. Der Einfluss von Prozessparametern und Systemzusam-mensetzung auf das Emulgierergebnis wird diskutiert und die Anwendbarkeit des Verfahrens für polymere Mikropartikeln anhand von Polypropylen (PP) und Polyethylen (PE-HD) dargestellt. Die erhaltenen Suspensionen werden zur Überführung in Pulverform sprühgetrocknet und die Fließeigenschaften des Pulvers analysiert. Durch trockenes Beschichten mit pyrogener Kieselsäure kann die Fließfähigkeit der erhaltenen Partikeln weiter verbessert werden. Das Verfahren bietet somit einen neuen Zugang zur Herstellung neuer Ausgangsmaterialien für die Additive Fertigung.<br

Increasing flowability and bulk density of PE-HD powders by a dry particle coating process and impact on LBM processes - Blümel, Christina; Sachs, Marius; Laumer, Tobias; Winzer, Bettina; Schmidt, Jochen; Schmidt, Michael; Peukert, Wolfgang; Wirth, Karl-Ernst (Rapid Prototyping Journal, 2015)
Purpose - The purpose of this paper is to demonstrate the processability of cohesive PE-HD particles in laser beam melting processes (LBM) of polymers. Furthermore, we present a characterization method for polymer particles, which can predict the quality of the powder deposition via LBM processes. Design/methodology/approach - This study focuses on the application of dry particle coating processes to increase flowability and bulk density of PE-HD particles. Both has been measured and afterwards validated via powder deposition of PE-HD particles in a LBM machine. Findings - For efficient coating in a dry particle coating process, the PE-HD particles and the attached nanoparticles need to show similar surface chemistry, i.e. both need to behave either hydrophobic or hydrophilic. It is demonstrated that dry particle coating is appropriate to enhance flowability and bulk density of PE-HD particles and hence considerably improves LBM processes and the resulting product quality. Originality/value - At present, in LBM processes mainly polyamide (PA), 12 particles are used, which are so far quite expensive in comparison to, for example, PE-HD particles. This work provides a unique and versatile method for nanoparticulate surface modification which may be applied to a wide variety of materials. After the coating, the particles are applicable for the LBM process. Our results provide a correlation between flowability and bulk density and the resulting product qualit
Keywords: Bulk density; Dry particle coating; Flowability; Hydrophilic; Hydrophobic; Polymers

Influence of laser power fluctuations on the quality of additive manufactured workpieces - Heinl, Martin; Galovskyi, Bogdan; Bayer, Florian; Laumer, Tobias; Hausotte, Tino (Lasers in Manufacturing (LiM), 2017)
There is a great potential in selective laser sintering (SLS) processes caused by increasing application areas in the field of additive manufacturing (AM). The related requirements to the quality of additive manufactured workpieces can be attributed to its process parameters. In this context, the examination of laser power fluctuations is interesting because of its direct influence on the workpiece quality. If the planar energy input into the powder bed is not constant, local areas can melt inhomogeneously beside the expected gauss-distributed intensity profile of the laser spot. For quality assessment a testing workpiece and its manufacturing strategy have been developed to measure the interactions between laser power and dimensional accuracy. Initially the appearing losses of the laser power in the beam path have been observed to optimize the energy input. In addition to the warm-up behaviour of the CO2-laser, appearing energy peaks during short-term sequences also show an influence on the workpiece quality. Finally in post-process quality assessment, the correlations of laser power with the dimensional accuracy and surface roughness are analysed by optical fringe projection and focus variation techniqu
Keywords: CO2-Laser; selective laser sintering (SLS); energy input; laser power fluctuation; dimensional deviation

Laser beam melting of multi-material components - Laumer, Tobias; Karg, Michael; Schmidt, Michael (Physics Procedia, 2012)
First results regarding the realisation of multi-material components manufactured by Laser Beam Melting of polymers and metals are published. For realising composite structures from polymer powders by additive manufacturing, at first relevant material properties regarding compatibility have to be analysed. The paper shows the main requirements for compatibility between different materials and offers first results in form of a compatibility matrix of possible combinations for composite structures. For achieving gradient properties of additively manufactured metal parts by using composite materials the composition of alloying components in the powder and adapted process strategies are varied. As an alternative to atomizing pre-alloyed materials, mixtures of different powders are investigated.
Keywords: Additive Manufacturing; Laser Beam Melting; New Materials

Modeling of Laser Beam Absorption in a Polymer Powder Bed - Osmanlic, Fuad; Wudy, Katrin; Laumer, Tobias; Schmidt, Michael; Drummer, Dietmar; Körner, Carolin (Polymers, 2018)
In order to understand the absorption characteristic, a ray trace model is developed by taking into account the reflection, absorption and refraction. The ray paths are resolved on a sub-powder grid. For validation, the simulation results are compared to analytic solutions of the irradiation of the laser beam onto a plain surface. In addition, the absorptance, reflectance and transmittance of PA12 powder layers measured by an integration sphere setup are compared with the numerical results of our model. It is shown that the effective penetration depth can be lower than the penetration depth in bulk material for polymer powders and, therefore, can increase the energy density at the powder bed surface. The implications for modeling of the selective laser sintering (SLS) process and the processability of fine powder distributions and high powder bed densities are discussed.
Keywords: additive manufacturing; laser absorption; powder bed; polyamide 12; PA12

Optical analysis of polymer powder materials for Selective Laser Sintering - Laumer, Tobias; Stichel, T.; Nagulin, K.; Schmidt, Michael (Polymer Testing, 2016)
This study increases the basic understanding of optical material properties of polymer powders used in selective laser sintering (SLS). Therefore, different polymer powder materials were analyzed regarding their optical material properties with an integration spheres measurement setup. By the measurements a direct connection between the absorption behavior of the solid material and the overall optical material characteristics of the same material in powdery form could be shown. The results were used to develop an advanced explanation model for the optical material properties of powders. At present, existing explanation models only consider the occurring of multiple reflections in the gaps between the particles to explain the overall optical material properties of powder materials. Thus, by also considering the absorption behavior of the single particles, the basic understanding of the beam-matter interaction and their effect on the optical material properties of powder materials can be expanded.
Created from Fastlane, Scopus look-up
Keywords: Additive manufacturing; Integration spheres; Material qualification; New materials; Optical material characteristics; Selective Laser Sintering

Qualification and modification of new polymer powders for laser beam melting using Ulbricht spheres - Laumer, Tobias; Stichel, Thomas; Sachs, Marius; Amend, Philipp; Schmidt, Michael (2013)

Qualification and modification of new polymer powders for laser beam melting using Ulbricht spheres - Laumer, Tobias; Stichel, T.; Sachs, Marius; Amend, P.; Schmidt, Michael (High Value Manufacturing: Advanced Research in Virtual and Rapid Prototyping - Proceedings of the 6th International Conference on Advanced Research and Rapid Prototyping, VR@P 2013, 2014)
The restricted amount of available materials for Laser Beam Melting (LBM) of polymers is one of the main limitations for expanding the technology. Current qualification methods deal with problems like inadequate powder flowability or high part porosities among others but do not offer a detailed analysis of the important beam-matter-interaction between powder particles and electro-magnetic laser radiation. In this paper, polyethylene powder is qualified for the LBM process and specifically analyzed regarding the optical material properties of the powder for a wavelength of 10.6 μm. By admixing graphite as absorption intensifier the change of the optical material properties and the thereby connected processing parameters are analyzed. Furthermore an explanation approach is given to explain the relation between different transmittances of different powder particles and the optical material properties of the polymer powders. © 2014 Taylor & Francis Group.
CRIS-Team Scopus Importer:2023-03-07

Realization of multi-material polymer parts by simultaneous laser beam melting - Laumer, Tobias; Stichel, Thomas; Riedlbauer, Daniel-Rouven; Amend, Philipp; Mergheim, Julia; Schmidt, Michael (Journal of Laser Micro Nanoengineering, 2015)
In this paper, first results regarding the realization of multi-material parts by Simultaneous Laser Beam Melting (SLBM) of polymers are presented. This new approach allows the layerwise generation of parts consisting of different polymer materials within one building process. Besides the typical advantages of additive manufacturing technologies, such parts can fulfill different product requirements concomitant and therefore could enlarge the overall field of application. The powder materials used for this paper are polyethylene (PE) and a polyamide based thermoplastic elastomer (TPE). After depositing the powder materials next to each other, infrared-emitters heat the lower melting polymer and a CO2 laser provides the preheating temperature of the higher melting polymer. In the last step, a thulium fibre laser melts the two preheated powders simultaneously. The realized specimens are characterized by cross sections and their tensile strengths are determined. Additionally, the new approach of the simultaneous energy irradiation is investigated using a Finite Element Analysis in order to gain a more profound process understanding. In that sense, the influence of the size of the exposure area on the reachable maximum temperatures inside that area was analyzed by the simulation and compared to experimental studies.
UnivIS-Import:2015-07-08:Pub.2015.tech.FT.FT-TM.realiz
Keywords: Additive manufacturing; Multi-material parts; New materials; Simultaneous laser beam melting of polymers

Simultaneous laser beam melting of multimaterial polymer parts - Laumer, Tobias; Stichel, Thomas; Amend, Philipp; Schmidt, Michael (Journal of Laser Applications, 2015)
By simultaneous laser beam melting (SLBM), parts consisting of different polymer powders can be additively manufactured within one building process. Besides the advantages of conventional LBM, e.g., not needing additional tools and being able to realize parts with almost any geometry, different product requirements can be achieved within a single part. Product requirements may be different chemical resistances or haptic material properties. Therefore, SLBM enlarges the application field for additive manufacturing in general. In the process, two different materials are deposited on the building platform and preheated a few degrees below the melting temperature of the lower melting polymer by infrared emitters. Afterward, a CO2 laser (λ=10.6μm) provides the energy for the temperature difference between the preheating temperatures of both materials. Finally, a digital light processing chip is used to achieve simultaneous and flexible energy deposition for melting both preheated polymers. By illuminating the chip with a laser, parts of the beam can be flexibly guided onto the powder bed or into a beam trap. As laser, a single mode thulium laser (λ=1.94μm) is used. After melting the layer, a new layer is deposited and the process starts anew. In this paper, polypropylene and polyamide 12 are used as materials. After analyzing the material and melting behavior during the process by a high-resolution thermal imaging system, the parts are qualified regarding their material compatibility at the boundary zone and porosity by cross sections.
Created from Fastlane, Scopus look-up
Keywords: additive manufacturing; material qualification; multi-material parts; new processes

Temperature-dependent optical material properties of polymer powders regarding in-situ measurement techniques in additive manufacturing - Heinl, Martin; Laumer, Tobias; Bayer, Florian; Hausotte, Tino (Polymer Testing, 2018)
Due to the growing number of applications for Additive Manufacturing (AM), an increasing need for enhanced quality control methods exists. Here optical measurement techniques are often used for in-situ monitoring in AM. There is a great potential to standardize and improve applications of optical measurement devices in accordance to the increasing requirements of measuring tasks. Beside the optical material qualifications, especially process-oriented changes in optical effects are of great relevance for in-situ evaluations. The optical modifications may be attributed to aggregate specific phase transitions coming along with variable emitted wavelengths. A measuring setup with two integrations spheres and a heated process chamber have been developed to analyze the optical interactions of laser radiation and visual illumination with the powder. The process oriented analysis for selective laser sintering lead to improved operating conditions in the field of in-situ measurements in combination with an accurate evaluation of the absorption ratio of the examined powde
Keywords: Additive Manufacturing; Selective Laser Sintering; In-Situ Measurement; Process-Oriented Optical Material Qualifica-tion; Integration Spheres